Antara Yogyakarta dan Jakarta: Campur Kode dan Domestikasi Bahasa Jawa dalam Iklan Tokopedia - Munfa’ati Muadibah; Miranti Widyaningsih; Assolatu Jamiah; Asep Abbas Abdullah (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2020)
The sociolinguistic paradigm forms the background of this study. Code switching in advertisements is an interesting thing because it actually shows the interrelation between major and minor languages which are in Indonesian and Javanese. On the other hand, code switching is a linguistic phenomenon that is closely related to certain social situations. The object in this study is the Tokopedia advertisement